Urban growth, population, and recession: Unveiling multiple spatial patterns of demographic indicators in a Mediterranean City. Issue 8 (22nd May 2017) - Salvati, Luca; Carlucci, Margherita
Abstract: Recessions have traditionally influenced population dynamics, leading to increasing social disparities and a polarised distribution of economic activities. This study identifies differences in short‐term demographic trends before and during the 2007 recession in a metropolitan area of southern Europe. Using vital statistics, indicators were calculated over two distinct time intervals representative of expansion (2000–2007) and recession (2008–2014) waves in Athens, Greece, at the spatial scale of municipalities. Local‐scale changes in population dynamics were considered key indicators to evaluate the crisis' impact on recent urban transformations. Demographic polarisations in urban and rural areas have progressively increased the gap between wealthy and economically disadvantaged districts. In Athens, short‐term population dynamics were influenced by a combination of socioeconomic factors and processes acting at different spatial scales due to suburbanisation, recession, and demographic transition. As a result, the use of nonlinear analysis proves to be a useful tool to investigate urban systems in their complexity and supports the debate over the future development of contemporary cities.